PENGGUNAAN TERAPI SEFT (SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE) DALAM MEMPERBAIKI KUALITAS TIDUR DAN STABILITAS TEKANAN DARAH: LITERATURE REVIEW - Ramadina, Rizma Dwi; Rebti Sari, Eka Dwi Ajeng; Fatmawati, Nur Azizah; Dianova, Vivi Uma; Ditiya, Rista Dwi Wahyu (Coping: Community of Publishing in Nursing; Vol 10 No 3 (2022): Juni 2022, 2022)
Spiritual Emotional Freedom Technique is a relaxation technique that combines body system techniques with spiritual healing that uses emphasis on certain points on the body. Spiritual Emotional Freedom Technique helps individuals to be free from emotional stress (negative energy), because it causes increased blood pressure in hypertensive patients and causes sleep quality disorders. The purpose of the literature review was analyzed the impact of SEFT in improving sleep quality and blood pressure stability. Literature review using electronic data search using databases, namely Google Scholar and Garuda (Digital Reference Garba). The keywords used are "quality of sleep", "Spiritual Emotional Freedom Technique", "blood pressure stability", which have inclusion criteria, namely journals published in the last 7 years, using Indonesian language, and have exclusion criteria, namely systematically sorting out journals according to the topic. Results from 4 journals that have been found show that the use of SEFT therapy can improve sleep quality and reduce blood pressure. The use of Spiritual Emotional Freedom Technique (SEFT) therapy is very suitable and recommended for the elderly to improve sleep quality and blood pressure. SEFT therapy only needs to be done every day for 5-15 minutes.